American Political Parties Why They Formed, How They Function, and Where They're Headed - White, John Kenneth (University Press of Kansas, 2022)
American Political Parties is a core textbook on political parties in the United States that places the US party system into a framework designed around the disagreements between Alexander Hamilton and Thomas Jefferson. White and Kerbel argue that the two-party system in the United States began with a common agreement on the key values of freedom, individual rights, and equality of opportunity but that Hamilton and Jefferson disagreed-often vehemently-over how to translate these ideals into an acceptable form of governance. This text develops a unique historical perspective of US party development using the disagreements between Alexander Hamilton and Thomas Jefferson as a framework for analysis. While Hamilton wanted to marry freedom to a strong, active federal government with an energetic president who would act on behalf of all citizens, Jefferson believed that freedom should be allied to local civic virtue, with governmental responsibilities placed primarily at the local level. Today, Hamiltonian nationalism finds its home in the Democratic Party, while Republicans have espoused Jeffersonian localism since 1964. Using this historical framework, American Political Parties examines a range of topics including marketing and social media, campaign finance, reforms in the presidential nominating process, political demography, and third parties. In this new edition (previously published as Party On!), the authors describe four possible futures in the wake of the 2020 election and why Americans believed it was "the most important" election in their lifetimes. The unique history of US political parties as set forth by the disagreements between Alexander Hamilton and Thomas Jefferson is at an inflection point. Republicans have become an insurgent party fully under the control of Donald Trump while Democrats have an opportunity to create a new majority coalition. This juncture poses unique challenges to our democracy and constitutional framework, and the book describes four possible outcomes, postulating where American political parties are headed in this decade. This book is published as part of the Sustainable History Monograph Pilot, with the generous support of the Andrew W. Mellon Foundation.